FRACTAL PRINCIPLE FOR DESIGN OPTIMIZATION OF STRUCTURAL KNOWLEDGE - Булгакова, Н. Б. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
This article explains how to use the fractal principle of natural systems and proportions to form the structure of the content of academic disciplines in the preparation of the future experts of high school. Obtained philosophical categories as components of the structure of the content of academic disciplines that provide the opportunity to form an optimal structure of the whole content of the discipline, or by a separate information, if their ratios correspond to mathematical laws of natural systems such as the F module or wurf